Analisis Kondisi Fisik dan Keterampilan Teknik Dasar Sepak Bola pada Pemain Level Junior - Ngisomudin Ngisomudin; Yudhi Purnama; Sofyan Ardyanto; Riki Edo Saputro (Universitas Hamzanwadi, 2026)
The training of young soccer players is often suboptimal because training programs are designed without objective data on the players' initial conditions. This study aims to analyze the physical condition and basic technical skills of players at the Ganesha Soccer School (SSB) as a basis for evaluating the training program. A quantitative approach with descriptive methods was used in this study. The population consisted of all Ganesha SSB players, with a sample of 20 people taken using total sampling. The research instruments included physical condition tests (agility, explosive power, reaction time, speed, endurance, strength) and basic technical skill tests (ball control, dribbling, heading, long pass, short pass, shooting). The data were analyzed using descriptive statistics in the form of frequency distribution, percentage, mean, and standard deviation. The results showed that the players' physical condition was dominated by the poor category (40%), with the main weaknesses being speed (75% poor to very poor) and strength (100% poor). The majority of players' basic technical skills were in the moderate category (50%), with critical weaknesses in ball control (85% very poor) and short passes (50% poor). The conclusion of this study is that the physical abilities and basic technical skills of SSB Ganesha players in general still need to be significantly improved through a structured training program with a priority on developing speed, strength, ball control, and passing accuracy.